2019
DOI: 10.32098/mltj.02.2018.08
|View full text |Cite
|
Sign up to set email alerts
|

Box-loop technique in the management of complex elbow instability: a prospective controlled trial

Abstract: Introduction: Chronic elbow instability is a disable complication. This prospective study reports our experience with the box-loop reconstruction technique, compared with traditional Lateral Collateral Ligament (LCL) and eventual Medial Collateral Ligament (MCL) reconstruction, showing its functional outcome at 12-month follow-up. Methods: From January 2013 to February 2017, 27 patients with complex elbow instability were recruited. Group-A patients were managed using box-loop technique; in Group-B patients LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Our study is limited by the small number of subjects. However, our findings confirm the data reported by Finkbone et al 6 and Vicenti et al, 7 which found satisfactory short-term outcomes of box-loop reconstruction. Further studies with larger samples and longer follow-up are required to better investigate the efficacy and safety of this technique.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study is limited by the small number of subjects. However, our findings confirm the data reported by Finkbone et al 6 and Vicenti et al, 7 which found satisfactory short-term outcomes of box-loop reconstruction. Further studies with larger samples and longer follow-up are required to better investigate the efficacy and safety of this technique.…”
Section: Discussionsupporting
confidence: 93%
“…Two studies have performed this technique in chronic elbow instability, and it is found to be a safe and effective technique. 6,7 In this series, we describe our experience in treating patients with chronically unreduced elbow dislocation using box-loop ligament reconstruction. To our knowledge, this is the first report of patients with such conditions undergoing box-loop reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with chronic pain, joint instability, recurrent subluxation/dislocation, and limited range of movement, thus affecting patients' daily lives. 17 This systematic review focused on cases with PLRI managed by LUCLR. It is to be noted that results of articles on LUCLR for PLRIE were mainly published in case reports or series, 18,19 which were excluded from the present systematic review.…”
Section: Discussionmentioning
confidence: 99%